Personification as the Way of Grammatical Gender Category Expression in Art Context - Nurullina, Guzel M.; Erofeeva, Irina V.; Islamova, Elvira A.; Yuan, Tao (Journal of History Culture and Art Research, 2017)
The study of grammatical categories in the artistic context from the position of anthropocentrism is a topical issue in modern linguistics. The greatest interest from the point of view of the relationship "language" - "man" is the category of Russian language gender, which has great stylistic resources and can be motivated extra-linguistically. In this paper, the authors analyze personification as the way of gender grammatical category expression in the artistic context of Russian writer and poet works. In the article the authors consider the linguistic picture of the world, in the creation of which the embodiment is important, the semantic-grammatical properties of which are determined by the ambivalence of animacy-inanimation category. Gender denotation occupies a special place in the interpretative structure of gender category, which presupposes a nominative significance of neutral gender nouns as a result of personification, stylization and the expression of symbolic meaning. Thus, extralinguistic possibilities of gender category are expanded, which are realized mainly in artistic speech. The authors of the article conclude that the grammatical personification of gender category as a vivid means of expression, expressiveness, imagery and emotionality is associated with a person's thinking, his worldview, psychological characteristics; and this judgment allows us to consider the category of gender not only as a morphological one, but also as a logical, mental category.